Myeloid cell transformation by ras-containing murine sarcoma viruses. - Pierce, J H (1985)
BALB and Harvey murine sarcoma viruses contain ras transforming genes capable of altering the proliferation and differentiation of cells within the erythroid and lymphoid lineages (W. D. Hankins and E. M. Scolnick, Cell 26:91-97, 1981; J. H. Pierce and S. A. Aaronson, J. Exp. Med. 156:873-887, 1982; E. M. Scolnick et al., Mol. Cell. Biol. 1:68-74). The present studies demonstrate hematopoietic targets of ras-containing viruses within the myeloid lineage. Diffuse colonies were induced by BALB or Harvey marine sarcoma virus infection of murine bone marrow cells. Generally, these colonies were made up of relatively mature macrophages which exhibited increased self-renewal capacity but eventually underwent terminal differentiation in culture. Cells from one BALB murine sarcoma virus-induced colony displayed phenotypic markers of more immature myelomonocytic cells. This colony, designated BAMC1, readily established as a continuous cell line and was highly malignant in vivo. Exposure of these cells to 12-O-tetradecanoylphorbol-13-acetate led to the induction of a more mature myeloid phenotype, which was associated with decreased growth potential in vitro and in vivo. The effects of the inducing agent were not mediated by an alteration in the level of expression of the ras-coded p21 transforming protein. Our present findings extend the spectrum of targets whose growth is altered by ras-containing retroviruses to cells at several stages of differentiation within each of the major hematopoietic lineages.